Factors Associated With Depressive Episode Recurrences in Primary Care: A Retrospective, Descriptive Study - Nuggerud-Galeas, Shysset; Oliván Blázquez, Bárbara; Perez Yus, María Cruz; Valle-Salazar, Begoña; Aguilar-Latorre, Alejandra; Magallón Botaya, Rosa (Frontiers in Psychology, 2020)
Introduction and objective: The early identification of depressive patients having a poor evolution, with frequent relapses and/or recurrences, is one of the priority challenges in the current study of high prevalence mental disorders, and specifically in depression. So, this study aims to analyze the factors that may be associated with an increased risk of recurrence of major depression episodes in patients treated in primary care. Methods: A longitudinal retrospective study of cases-controls was proposed. The cases consisted of patients who had been diagnosed with major depression and who had presented recurrences (n=101), in comparison with patients who had experienced a single major depression episode with no recurrence (n=99). The variables of the study are: age at first episode, number of episodes, perception of severity of the depression episode suffered prior to recurrence, number of residual symptoms, physical and psychiatric comorbidity, history of anxiety disorders, family psychiatric history, high incidence of stressful life events (SLEs), and experiences of physical, psychological or sexual abuse in childhood. The differences of the variables were compared between the case subjects and the control subjects, using the Mann-Whitney, Chi square and Fisher U statistics. A multivariate analysis (ordinary logistic regression) was performed. Results: The average age of those suffering more than one depressive episode is significantly older (5 years) and a higher percentage of subjects who have experienced more than one depressive episode have a history of anxiety disorders. In the multivariate analysis, the variables that obtained a significant value in the logistic regression analysis were age (OR: 1.03; value: 0.007) and having suffered sexual abuse during childhood (OR: 1.64; value: 0.072). Conclusion: These indicators should be considered by primary care physicians when attending patients suffering from major depression.